EFEKTIVITAS PEMBELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL PADA MATERI TEKS HIKAYAT KELAS X TAHUN PELAJARAN 2026/2027 - Shinta Aprilia; Chindy Aulia; Faiqotul Hasanah; Maulida Putri Amelia; Abdul Wahab (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to examine the effectiveness of using audiovisual media in improving the learning outcomes, interest, and comprehension of 10th-grade students in Class X-B at MA At-Taufiqiyah regarding hikayat texts during the 2026/2027 academic year. The background of this study stems from students’ low comprehension of hikayat texts due to the use of Classical Malay, which is difficult to understand, and conventional teaching methods. This study employs a quantitative research design with a descriptive approach. Data were collected through observation, teacher interviews, documentation, and the distribution of a questionnaire containing 10 items to 18 students in Class X-B. The data analysis techniques used include frequency distribution tables and descriptive analysis. The results indicate that the use of audiovisual media (such as videos and short films) proved highly effective. A total of 100% of the students (18 students) gave positive responses and agreed that audiovisual media makes learning less boring, sparks curiosity, and makes it easier for them to visualize characters, understand complex storylines, and discover the intrinsic and extrinsic values of the narrative texts. Thus, the use of audiovisual media has successfully improved students’ understanding and learning outcomes significantly at MA At-Taufiqiyah.